TMF is a golgin that binds Rab6 and influences Golgi morphology - Fridmann-Sirkis, Yael (BMC Cell Biol, 2004)
BACKGROUND: Golgins are coiled-coil proteins associated with the Golgi apparatus, that are believed to be involved in the tethering of vesicles and the stacking of cisternae, as well as other functions such as cytoskeletal association. Many are peripheral membrane proteins recruited by GTPases. Several have been described in animal cells, and some in yeast, but the relationships between golgins from different species can be hard to define because although they share structural features, their sequences are not well conserved. RESULTS: We show here that the yeast protein Sgm1, previously shown to be recruited to the Golgi by the GTPase Ypt6, binds to Ypt6:GTP via a conserved 100-residue coiled-coil motif that can be identified in a wide range of eukaryotes. The mammalian equivalent of Sgm1 is TMF/ARA160, a protein previously identified in various screens as a putative transcription or chromatin remodelling factor. We show that it is a Golgi protein, and that it binds to the three known isoforms of the Ypt6 homologue Rab6. Depletion of the protein by RNA interference in rat NRK cells results in a modest dispersal of Golgi membranes around the cell, suggesting a role for TMF in the movement or adherence of Golgi stacks. CONCLUSION: We have identified TMF as an evolutionarily conserved golgin that binds Rab6 and contributes to Golgi organisation in animal cells.